SUBSTANTIATION OF THE CHOICE OF COATING MATERIAL WHEN RESTORING PARTS OF AGRICULTURAL MACHINERY BY COLD GAS-DYNAMIC SPRAYING - KUCHERENKO, Jylia (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Based on the method of cold gas-dynamic spraying, technologies are being created to solve problems of energy and resource saving in various industries and non-traditional and effective methods of production, repair, restoration, anti-corrosion protection, obtaining electrical and heat-conductive, anti-friction and other coatings of functional units, and as well as elements of a wide variety of machinery and equipment. The main feature of cold gas-dynamic spraying is the absence of high temperatures during the formation of metal coatings, therefore, the absence of oxidation of particle and base materials, non-equilibrium crystallization processes, and high internal stresses in the workpieces. Coatings created in this way are a metal matrix with ceramic particles embedded in it. They are characterized by high strength, good performance properties and can be applied in any thickness. One of the important characteristics of coatings is the adhesion strength. Before spraying on any part, it is necessary to find out which coating material will give the best strength characteristics between the two materials. Therefore, before spraying, it is important to study the specifics of the formation of a durable coating for a given part, as well as to compare the strength characteristics of the cold gas-dynamic spraying method with other methods for restoring parts. In this paper, an analysis of various coating materials used in the restoration of parts by the method of cold gas-dynamic spraying is carried out. The strengths and weaknesses of various coating technologies are determined, as well as recommendations for choosing a material when restoring parts by cold gas-dynamic spraying.